2014
DOI: 10.1073/pnas.1412840111
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinases regulate lysosomal degradation of hypoxia-inducible factor 1α to promote cell-cycle progression

Abstract: Hypoxia-inducible factor 1 (HIF-1) is a transcription factor that mediates adaptive responses to oxygen deprivation. In addition, the HIF-1α subunit has a nontranscriptional role as a negative regulator of DNA replication through effects on minichromosome maintenance helicase loading and activation. However, some cell types continue to replicate under hypoxic conditions. The mechanism by which these cells maintain proliferation in the presence of elevated HIF-1α levels is unclear. Here we report that HIF-1α ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 57 publications
(64 reference statements)
3
63
1
Order By: Relevance
“…Recently, an O 2 -independent mechanism of HIF protein degradation has been described involving lysosomes (15)(16)(17)(18). Because an acidic environment is optimal for lysosomal functioning, we focused on this particular non-canonical HIF degradative pathway (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an O 2 -independent mechanism of HIF protein degradation has been described involving lysosomes (15)(16)(17)(18). Because an acidic environment is optimal for lysosomal functioning, we focused on this particular non-canonical HIF degradative pathway (37).…”
Section: Resultsmentioning
confidence: 99%
“…HIF regulates the transcription of a host of targets, including those with angiogenic, vasodilatory, inflammatory, and glycolytic functions (13)(14). Recently, evidence has emerged for a separate O 2 -independent, non-canonical HIF degradation pathway that is reliant on chaperone-mediated lysosomal autophagy (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…The targets of HIFs include genes controlling vascularization, cellular proliferation, migration, and metabolism (6)(7)(8)(9)(10)(11). A wellcharacterized animal model of hypoxia-induced pulmonary hypertension involves exposure to chronic hypoxia (CH), typically 10-12% inspired oxygen.…”
mentioning
confidence: 99%
“…26 Studies demonstrated that cells in hypoxic regions tend to be arrested at G1 phase. 9,27,28 Paclitaxel was found to stabilize cytoplasmic microtubules, thus the cells would stagnate at the beginning of M phase, followed by induction of apoptosis and/or mitotic catastrophe. 29 According to our results, the antiproliferative effect of paclitaxel was attenuated under hypoxia ( Figure 1a), with IC 50 increasing around threefolds.…”
Section: Discussionmentioning
confidence: 99%